172 BRAIN NATRIURETIC PEPTIDE: A SENSITIVE MONITOR IN PATIENTS WITH HYPOPLASTIC LEFT HEART SYNDROME. Issue 1 (1st January 2007) - Evans, W. N.; Mayman, G. A.; Acherman, R. J.; Luna, C. F.; Rothman, A.; Cass, K. A.; Kip, K. T.; Restrepo, H.
Abstract : Introduction: Amplified cardiac B-natriuretic peptide (BNP) expression results from ventricular volume or pressure overload. The literature reports limited experience with serial BNP levels in pediatric patients. We report a small series of patients with hypoplastic left heart syndrome (HLH) undergoing serial outpatient BNP monitoring. Objective: To identify the clinical usefulness of rapid, serial BNP-level monitoring in patients with complex congenital heart disease. Methods: Rapidly available fingerstick BNP levels were obtained in our in-office certified outpatient clinical laboratory. Results take less than 20 minutes. We analyzed 36 BNP values obtained in 12 patients with HLH. Results: Age ranged from 2 months to 8 years. Patients were status post stage I, II, or III HLH Norwood palliation, and all were on combination medical therapy, including angiotensin-converting enzyme inhibitors, digoxin, diuretics, and aspirin or Coumadin. Serial BNP levels were normal (20 ± 6 pg/dL) in 8 patients > 4 weeks after cardiac surgery. BNP levels were elevated (range 103-839 pg/dL) during serial evaluation in four patients, two with systemic pressure overload (one with systemic hypertension and one with residual coarctation) and two with volume overload (atrioventricular valve regurgitation [AVR]). Elevated BNP values decreased with adjustments to medical therapy in the patients with hypertension and AVR and by interventional cardiac catheterization in the patient with residual coarctation. Conclusions: BNP levels were normal in hemodynamically stable HLH patients. Abnormal BNP levels were a guide to clinical management. Prolonged pathologic loading conditions, especially in those patients with single right ventricles, may lead to ventricular dysfunction, congestive heart failure, and death. Predicting the potential for ventricular dysfunction is preferable to detecting its presence. Validation of the clinical usefulness of rapid, serial BNP level monitoring in patients with complex congenital heart disease warrants further study.